Postoperative Tachycardia in Head and Neck Microvascular Free Flap Patients. (5th February 2019) - Ziegler, Andrea; Schneider, Alexander; Pittman, Amy; Thorpe, Eric
Abstract : Objective: The goal of this study was to determine the incidence of postoperative tachycardia and its predictive value of complications in patients following microvascular free flap surgery in the head and neck. Study Design: Retrospective chart review. Setting: Single tertiary care academic medical center. Subjects and Methods: All patients who underwent a microvascular free flap of the head and neck by surgeons in the department of otolaryngology from 2013 to 2017 were included in this study. Results: Of the 344 who patients met inclusion criteria, 40.4% had a maximum heart rate (HR) of the hospitalization over 110 beats per minute (bpm). Patients with a maximum HR greater than 110 bpm were 19 times more likely to experience a composite vascular complication (myocardial infarction, myocardial necrosis, or pulmonary embolism) than patients with a maximum HR <110 bpm ( P =. 0063). Patients with a history of chronic kidney disease were also noted to have an increased risk of experiencing a postoperative composite vascular event. Conclusion: Postoperative tachycardia is significantly associated with adverse outcomes and should not be dismissed as a normal variant. Identifying patients at an increased risk of having an underlying complication can help guide interpretation, workup, and management of postoperative patients in the head and neck population.